Review of Australian genera Tessaromma Newman and Phlyctaenodes Newman with description of a new genus and species (Coleoptera: Cerambycidae: Cerambycinae: Phlyctaenodini) - Jin, Mengjie; Ślipiński, Adam; Keyzer, Roger De; Pang, Hong (Zootaxa, 2017)
Two Australian genera, Tessaromma Newman and Phlyctaenodes Newman of the tribe Phlyctaenodini Lacordaire, 1868 (=Tessarommatini Lacordaire, 1868) syn. nov. are revised. All known species are redescribed and illustrated. Keys to the genera of Australian Phlyctaenodini and species of Tessaromma Newman and Phlyctaenodes are provided. One new genus Escalonia gen. nov. (type species: Tessaromma loxleyae McKeown, 1942) and three new species Phlyctaenodes queenslandicus sp. nov., Escalonia carolinae sp. nov. and Escalonia surprise sp. nov. are described. Tessaromma truncatispina McKeown, 1940 is regarded as a junior synonym of Tessaromma sordida McKeown, 1940; Tessaromma nigroapicale Aurivillius, 1917 is synonymized with Tessaromma nanum Blackburn, 1899; and Tessaromma sericans (Erichson, 1842) is synonymized with Tessaromma triste (Hope, 1841). Tessaromma setosa McKeown, 1942 is moved to Ectinope Pascoe, and Zoedia intricata Gressitt, 1959 is moved to Escalonia gen. nov.